The New Politics of Fatherhood Men's Movements and Masculinities - Jordan, Ana.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2019)
This book makes a unique contribution to contemporary research into masculinities, men's movements, and fathers' rights groups. It examines the role of changing masculinities in creating equality and/or reinforcing inequality by analysing diverse men's movements, their politics, and the identities they (re)construct. Jordan advances a typology for categorising men's movements ('feminist', 'postfeminist', and 'backlash' movements) and addresses debates over the construction of 'masculinity-in-crisis', arguing that 'crisis' is frequently invoked in problematic ways. These themes are further explored through original analyses of material produced by 'feminist', 'postfeminist', and 'backlash' men's groups. The main empirical contribution of the book draws on interviews with fathers' rights activists to explore the (gendered) implications of the 'new' politics of fatherhood. The nuanced examination of fathers' rights perspectives reveals multiple, complex narratives of masculinity, fatherhood, and gender politics. The cumulative effect of these is, at best, postfeminist and depoliticising, and, at worst, another vitriolic 'backlash'. The New Politics of Fatherhood expands scholarly understandings of gender, masculinities, and social movements in the under-researched UK context, and will appeal to readers with interests in these areas.
1. Introduction -- 2. Gender, Social Movements and the Politics of Backlash -- 3. Masculinities in Crisis? -- 4. Feminist Men's Movements: The White Ribbon Campaign (UK) and the dilemmas of feminist men -- 5. Postfeminist Men's Movements: The Campaign Against Living Miserably and male suicide as "crisis" -- 6. Backlash Men's Movements Part 1: (Real) Fathers 4 Justice, bourgeois-rational and new man/new father masculinities -- 6. Backlash Men's Movements Part 2: (Real) Fathers 4 Justice, hypermasculinity, and fathers as superheroes -- 7. Conclusion.
Keywords: Sex; Sociology; Social groups; Gender Studies; Sociology of Family, Youth and Aging